PENGARUH KUALITAS PELAYANAN, LOKASI, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN MENGINAP DI HOTEL SRIWIJAYA JAKARTA - Fachri Nugraha; Sinthon Siahaan (LPPM Universitas Asa Indonesia, 2023)
The existence of this research is to be able to understand the effect of service quality, location, and price perceptions on the decision to stay at the Sriwijaya Hotel Jakarta. The population in this study were guest who came to visit during their stay from May 2023 to June 2023. The sampling technique used a random sample of 100 respondents. Data collection through random sampling using a questionnaire that has been tested for validity and reliability. Quantitative analysis with SPSS version 24 utilise multiple linear regression method. The results of this study indicate that service quality has a significant effect on the decision to stay and perceived price has a significant effect on the decision to stay, while location has no significant effect on the decision to stay.